Phase II trial of sorafenib and doxorubicin in patients with advanced hepatocellular carcinoma after disease progression on sorafenib. (25th August 2020) - El Dika, Imane; Capanu, Marinela; Chou, Joanne F.; Harding, James J.; Ly, Michele; Hrabovsky, Anna D.; Do, Richard K.G.; Shia, Jinru; Millang, Brittanie; Ma, Jennifer; O'Reilly, Eileen M.; Abou‐Alfa, Ghassan K.
Abstract: Background: Patients with advanced hepatocellular carcinoma (HCC) who received second line sorafenib plus doxorubicin following disease progression on sorafenib were shown retrospectively to have improved progression free survival (PFS) and overall survival (OS). Sorafenib plus doxorubicin combination may synergistically promote ASK‐1 mediated apoptosis in cancer cells through RAF‐1 inhibition. Thus, we conducted this phase II study of sorafenib and doxorubicin combination following progression on sorafenib. Methods: Patients with histologically confirmed advanced HCC, confirmed radiologic progression on sorafenib, Karnofsky performance status (KPS) ≥70%, and Child‐Pugh A liver cirrhosis were eligible. Patients received sorafenib 400 mg twice daily and doxorubicin 60 mg/m 2 once every 3‐weeks. The primary endpoint was OS at 6 months (OS6). Secondary endpoints included safety, PFS, OS, response rate (RR) by RECIST 1.1. Additional endpoints included baseline and on‐treatment tumor ASK‐1 and pERK expression levels by immunohistochemistry (IHC) and the correlation with PFS, RR, and OS. Results: Thirty patients were enrolled in the study, 86% were male, median age was 64 years. OS6 was 76.6% (95%CI: 57.2%‐88.1%). Median OS was 8.6 (95%CI: 7.3‐12) months, and median PFS reached 3.9 (95%CI: 2.4‐4.6) months. Three (11%) partial responses were observed and 17 patients (61%) had stable disease. Pertinent grade 3‐4 adverse events that occurred in more than 10% of patients included neutropenia (16%), febrile neutropenia (10%), anemia (10%), thrombocytopenia (10%), elevated AST (23%) and ALT (10%), hypophosphatemia (10%), and fatigue (10%). No association with the difference in baseline and post‐treatment ASK‐1 and pERK level of expression by IHC and survival outcomes was detected. Conclusion: Sorafenib plus doxorubicin following progression on sorafenib did not show any improved outcome. We do not recommend further development or use of this combination in HCC. Abstract : Sorafenib plus doxorubicin was evaluated as a second line therapy for advanced HCC. The association with the difference in baseline and post treatment ASK‐1 and pERK level of expression by IHC and survival outcomes was evaluated yet not detected. Sorafenib plus doxorubicin following progression on sorafenib did not show any improved outcome.